Political Consciousness in Ramdhari Singh Dinkar’s Kurukshetra: रामधारी सिंह दिनकर के कुरुक्षेत्र में राजनीतिक चेतना - Saxena, Priti (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In Ramdhari Singh Dinkar’s epic Kurukshetra, the war of the Mahabharata is presented not merely as a historical event, but as a symbol of political consciousness, moral conflict, and the responsibility of leadership. Through the depiction of war, Dinkar makes it clear that the struggle between power and morality cannot be separated. In his poetry, characters such as Dhritarashtra, Duryodhana, Arjuna, Karna, and Krishna are not included only for narrative purposes; rather, they symbolize power, moral conscience, and responsibility. The portrayal of war and politics in the poem serves as a means to awaken social and national consciousness. Arjuna’s dilemma, Karna’s sacrifice, and Krishna’s diplomacy convey the message that true leadership should not be driven by personal gain, but by the welfare of society and the nation. This research paper analyzes the various dimensions of political consciousness in Kurukshetra, such as the conflict between power and morality, the responsibility of leadership, and war as a source of social education. It also situates the work within the political and social context of post-independence India, a time when moral and political awareness was crucial for nation-building and the stability of democracy. Ultimately, Dinkar’s Kurukshetra is not merely a literary work, but also a source of political and moral education, offering relevant messages for contemporary society and leadership. Abstract in Hindi Language: रामधारी सिंह दिनकर के महाकाव्य कुरुक्षेत्र में महाभारत युद्ध को केवल ऐतिहासिक घटना के रूप में नहीं, बल्कि राजनीतिक चेतना, नैतिक संघर्ष और नेतृत्व की जिम्मेदारी के प्रतीक रूप में प्रस्तुत किया गया है। दिनकर ने युद्ध के माध्यम से यह स्पष्ट किया कि सत्ता और नैतिकता का संघर्ष अलग नहीं किया जा सकता। उनके काव्य में धृतराष्ट्र, दुर्योधन, अर्जुन, कर्ण और कृष्ण जैसे पात्र केवल कथानक के लिए नहीं, बल्कि सत्ता, नैतिक विवेक और जिम्मेदारी के प्रतीक हैं। कविता में युद्ध और राजनीति का चित्रण सामाजिक और राष्ट्रीय चेतना को जगाने का माध्यम है। अर्जुन का द्वंद्व, कर्ण का बलिदान और कृष्ण की कूटनीति यह संदेश देती हैं कि सच्चा नेतृत्व केवल व्यक्तिगत लाभ के लिए नहीं, बल्कि समाज और राष्ट्र के हित के लिए होना चाहिए। यह शोध पत्र कुरुक्षेत्र में राजनीतिक चेतना के विभिन्न आयामों का विश्लेषण करता है, जैसे: सत्ता और नैतिकता का द्वंद्व, नेतृत्व की जिम्मेदारी, युद्ध और सामाजिक शिक्षा। साथ ही इसे स्वतंत्र भारत के राजनीतिक-सामाजिक संदर्भ में रखा गया है, जब राष्ट्र निर्माण और लोकतंत्र की स्थिरता के लिए नैतिक और राजनीतिक जागरूकता अत्यंत महत्वपूर्ण थी। अंततः, दिनकर का कुरुक्षेत्र केवल साहित्यिक कृति नहीं, बल्कि राजनीतिक और नैतिक शिक्षा का स्रोत भी है, जो आज के समाज और नेतृत्व के लिए प्रासंगिक संदेश देता है। Keywords: रामधारी सिंह दिनकर, कुरुक्षेत्र, राजनीतिक चेतना, महाभारत, युद्ध और नैतिकता, नेतृत्व, सत्ता संघर्ष, समाज और राष्ट्र, नैतिक जिम्मेदारी, राष्ट्रीय जागरूकता।